PENGARUH DEPRESI TERHADAP TERJADINYA GINGIVITIS (Studi Terhadap Santri Pondok Pesantren Rohmatulla 2 Tahun 2012) - Yessi Idha Martha; Siti Chumaeroh; Aning Susilowati; Diyah Fatmasari (Jurnal Medali, 2013)
ABSTRACT Depression as a part of a psychological condition is a situation that interference with the natural feeling. Emotional condition can affect the secretion of saliva in oral cavity and can disrupt the balance of bacteria in the mouth and can cause disease in the oral cavity. One of the common diseases is gingivitis. The aim of this study is to determine the effect of depression on the occurrence of gingivitis at boarding school students Rohmatullah 2 in 2012.This study was used observational analytic method with cross sectional design study that was conducted on 50 students at the boarding school Rohmatullah2 in 2012 using simple random sampling method. The level of depression was measured with a questionnaire of Beck Depression Inventory (BDI). Gingival health conditions were measured by the Gingival Index. The results of research were analyzed using the Kolmogorov-Smirnovt test.The results of the data analysis with Kolmogorov-Smirnov test showed that there was a significant relationship between the level of depression and the occurrence of gingivitis (p=0.001), while the status of OHI-S as a confounding factor in this study also affect the occurrence of gingivitis (p=0.000). The existence of a significant effect of depression on the occurrence of gingivitis in accordance with a theory that depression can affect the release of cortisol from corticosteroid hormone that results in decreased production of IgA and Ig Gingingival fluid that acts as antibody in the oral cavity. In addition to the poor conditions of oral hygiene can lead the accumulation of plaque. from the accumulation of plaque can lead to the development of inflammatory diseases such as gingivitis.Based on the results of this study concluded that there was significant influence between depression and gingivitis at boarding school students Rohmatullah 2 in 2012.Â Keywords: Depression, Gingivitis, BDI, Gingival Index